2020
DOI: 10.3390/land9040118
|View full text |Cite
|
Sign up to set email alerts
|

Land Consolidation in Rural China: Life Satisfaction among Resettlers and Its Determinants

Abstract: The Chinese government has pursued rural land consolidation under the Building New Rural Communities (BNRC) initiative. The consolidation projects aim to address the hollowing village problem, improve the living standards of rural dwellers, and promote urban-rural integration. Rural villages with small populations and poor infrastructure are merged into a centralized rural community, and their inhabitants are resettled. The newly vacated buildings are then converted to agriculture land, which allows cities to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 44 publications
(47 reference statements)
1
11
0
1
Order By: Relevance
“…In detail, the estimated coefficients allowed to calculate the implicit WTA for compensating a given increment in LC. Our findings support previous studies showing that SWB is strongly linked to the satisfaction of basic human needs and to the social costs due to the loss of free resources (Aguado et al, 2018;Costanza et al, 2007;Hsu, 2019;Tay et al, 2015;Tong et al, 2020). This work has shown that the loss of undeveloped land, natural or semi-natural, has a value for the society.…”
Section: Discussionsupporting
confidence: 91%
“…In detail, the estimated coefficients allowed to calculate the implicit WTA for compensating a given increment in LC. Our findings support previous studies showing that SWB is strongly linked to the satisfaction of basic human needs and to the social costs due to the loss of free resources (Aguado et al, 2018;Costanza et al, 2007;Hsu, 2019;Tay et al, 2015;Tong et al, 2020). This work has shown that the loss of undeveloped land, natural or semi-natural, has a value for the society.…”
Section: Discussionsupporting
confidence: 91%
“…First, at the subsystem level, the findings show that economic development has been the key driver of rural development, whereas social development has relatively little impact. This result suggests that policymakers have neglected social development in rural areas, such as poverty reduction, social inclusion, and the provision of better welfare, which have become a hindrance to rural development [57,58]. In rural China, the problem of rural population aging and hollowing out is serious [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…For living needs, the Chinese government has established a rights-protection system for the elderly through the Law on Protection of the Elderly’s Rights and Interests, which emphasizes living care, health care, lifelong education, social participation, and spiritual support [ 22 ]. From the perspective of equity, urbanization resettlement guarantees elderly migrants’ rights to access public services, for example, basic medical care and livelihood security [ 23 , 24 ]. With improved living standards, some elderly migrants have changed their lifestyle to “urban elderly” and begun to pursue all aspects of high-quality public services [ 25 , 26 ].…”
Section: Literature Review and Research Methodsmentioning
confidence: 99%